Perancangan Aplikasi Sewa Alat Fotografi untuk Meningkatkan Pelayanan pada Konsumen Berbasis Website - Herli Herutomo; Zulfahmi Syahputra; Barany Fachri (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2025)
The advancement of information technology has driven many business sectors, including the equipment rental industry, to leverage digital platforms to enhance operational efficiency and customer service. This paper proposes the design of a photography equipment rental application based on a website, aimed at improving and accelerating the rental process while providing better service to customers. The application integrates features such as a product catalog, online booking, rental scheduling, payment system, and reminder notifications for equipment returns to ensure smooth transactions. Using a web-based system design approach, this application is expected to simplify the process for customers to select and rent photography equipment according to their needs, while minimizing errors and inconsistencies in the rental process. Additionally, this system aims to improve data management and equipment rental monitoring, enabling faster decision-making and enhancing customer satisfaction. The outcome of this application development is expected to have a positive impact on improving the quality of photography equipment rental services, ultimately increasing customer loyalty and business growth in the photography equipment rental industry